Sport and Humanism - Kürner, Darja (Array, 2011)
Tuning Educational Structures in Europe started in 2000 as a project to link the political objectives of the Bologna Process and at a later stage the Lisbon Strategy to the higher educational sector. Over time tuning has developed into a process, an approach to redesigning, develop, implement, evaluate and enhance quality first, second and third cycle degree programmes. As a result of Bologna Process the educational systems in all European countries are in the process of reforming, which are at the closing stage.This is the direct effect of the political decision to converge the different national systems in Europe. For Higher Education institutions these reforms mean the actual starting point for another discussion: the comparability of curricula in terms of structures, programmes, and actual teaching. The main aim of the Bologna Process is to create a European Higher Education Area based on international cooperation and academic exchange that is attractive to European students and staff as well as to students and staff from other parts of the world. The Bologna process is named after the Bologna Declaration, which was signed in the Italian city of Bologna on 19 June 1999 by ministers in charge of higher education from 29 European countries. Today the Process unites 47 countries all party of the European Cultural Convention and Committed to the goals of the European Higher Education Area. As part of the methodology tuning has developed reference points for first and second cycle programmes for generic and subject specific competences. In the framework of the tuning project European Credit Transfer System (ECTS) has been developed further as an accumulation system by linking credits to learning outcomes. This paper reflects how to implant Sport and Physical Education in University Curriculum. The Bologna Process gives us a new opportunity to enrich Physical Education and Sport with the theoretical contents from basic humanistic, sociological and natural sciences. At the Faculty of Arts, University of Ljubljana we designed model curriculum for chosen subject Sport and Humanism which contains theoretical chapters from Philosophy, Sociology, Medicine and Prevention and a wide selection of sports. The subject Sport and Humanism represent a link between theoretical sciences and physical practices and shows the interdisciplinary of sport which is one of the students most popular activities. The subject immediately became very popular between students of all grades and also among students top athletes who can gain credit points for their competitive sport activities.